Risk Factors of Transient Cortical Blindness After Cerebral Angiography: A Multicenter Study - Li, Miao; Liang, Huaxin; Liu, Chao; Liu, Hongtao; Zheng, Yang; Shi, Wanchao; Wang, Jie (Frontiers in Neurology, 2019)
Abstract Background: Although transient cortical blindness is a rare complication following cerebral angiography, identification of risk factors for the development of transient cortical blindness after cerebral angiography is an important clinical issue. Material and methods: Between January 2008 and April 2018, 5,126 patients at five high-volume medical centers who underwent cerebral angiography procedures were enrolled in this multicenter cohort study. Patient baseline characteristics and surgery-related factors were analyzed. We used multivariate logistic regression to examine factors associated with transient cortical blindness. Results: Eighteen patients (0.35%) in the total cohort of 5,126 suffered transient cortical blindness. After univariate statistical analysis, no significant differences were determined between the transient cortical blindness group and the control group regarding gender (p=0.454), age (p=0.872), smoking (p=0.170), diabetes (p=0.800), and hypertension (p=0.100). Compared with the control group, the transient cortical blindness group weighed less (p=0.020), and had larger dose of contrast agent (p=0.034) and more instances of contrast agent injected into the posterior circulation (p<0.001). Logistic regression analysis identified contrast agent dose and contrast agent injected into posterior circulation as independent predictive factors for transient cortical blindness (P<0.05). Conclusion: Larger dose of contrast agent and contrast agent injected into the posterior circulation are potential independent predictive factors for transient cortical blindness following cerebral angiography.